2018
DOI: 10.3390/genes9100507
|View full text |Cite
|
Sign up to set email alerts
|

Cupriavidus metallidurans Strains with Different Mobilomes and from Distinct Environments Have Comparable Phenomes

Abstract: Cupriavidus metallidurans has been mostly studied because of its resistance to numerous heavy metals and is increasingly being recovered from other environments not typified by metal contamination. They host a large and diverse mobile gene pool, next to their native megaplasmids. Here, we used comparative genomics and global metabolic comparison to assess the impact of the mobilome on growth capabilities, nutrient utilization, and sensitivity to chemicals of type strain CH34 and three isolates (NA1, NA4 and H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 81 publications
0
22
0
Order By: Relevance
“…Strain BS1 contained predicted intact prophages [Bacill_SP_15_ (NC_031245; 7), Burkho_phiE255 (NC_009237; 32), and Ralsto_RSA1 (NC_009382; 29)] as well as NA4, H1130 and Ni-2, detailed information of prophages is mentioned Table 5. Previous studies also provided evidence for the presence of prophages in other strains of C. metallidurans than strain CH34 (Van Houdt et al, 2018;Ali et al, 2019).…”
Section: Comparative Genome Plasticitymentioning
confidence: 85%
See 3 more Smart Citations
“…Strain BS1 contained predicted intact prophages [Bacill_SP_15_ (NC_031245; 7), Burkho_phiE255 (NC_009237; 32), and Ralsto_RSA1 (NC_009382; 29)] as well as NA4, H1130 and Ni-2, detailed information of prophages is mentioned Table 5. Previous studies also provided evidence for the presence of prophages in other strains of C. metallidurans than strain CH34 (Van Houdt et al, 2018;Ali et al, 2019).…”
Section: Comparative Genome Plasticitymentioning
confidence: 85%
“…ncc resistance determinant such as NreB, NccC, NccB, and NccA (Nickel-Cobalt-Cadmium Resistance Protein), showed a 100% identical AA sequence in both strains, CH34 and BS1. A nonsense/frameshift mutation in NccB, indicated to be present in strain CH34 and NA1, NA4, H1130 (Van Houdt et al, 2018) was also observed to be present in BS1. The smaller segment of NccB is 100% similar to the NccB segment in strain CH34 both by nucleotide and amino acid BLAST analysis but the larger locus was 99% similar, with one arginine replaced with isoleucine in BS1.…”
Section: (Supplementarymentioning
confidence: 89%
See 2 more Smart Citations
“…The genome-wide expression analysis of the silver-resistant mutant NA4S was previously performed via the microarray platform of the C. metallidurans type strain CH34 ( Mijnendonckx et al, 2019 ). However, taking into account the strain differences ( Van Houdt et al, 2018 ; Ali et al, 2019 ), we reassessed this more accurately via an RNA-seq approach. As the increased resistance stemmed from natural selection of resistance-conferring mutations ( Lenski, 2017 ), the global shift in transcriptome, resulting from the altered genotype of the evolved strain (NA4S) as compared with the parental strain (NA4), was examined in non-selective conditions ( Sandberg et al, 2014 ; LaCroix et al, 2015 ; McCloskey et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%